Shear-Activated Nanoparticle Aggregates Combined With Temporary Endovascular Bypass to Treat Large Vessel Occlusion. Issue 12 (December 2015) - Marosfoi, Miklos G.; Korin, Netanel; Gounis, Matthew J.; Uzun, Oktay; Vedantham, Srinivasan; Langan, Erin T.; Papa, Anne-Laure; Brooks, Olivia W.; Johnson, Chris; Puri, Ajit S.; Bhatta, Deen; Kanapathipillai, Mathumai; et al.
Abstract : Background and Purpose—: The goal of this study is to combine temporary endovascular bypass (TEB) with a novel shear-activated nanotherapeutic (SA-NT) that releases recombinant tissue-type plasminogen activator (r-tPA) when exposed to high levels of hemodynamic stress and to determine if this approach can be used to concentrate r-tPA at occlusion sites based on high shear stresses created by stent placement. Methods—: A rabbit model of carotid vessel occlusion was used to test the hypothesis that SA-NT treatment coupled with TEB provides high recanalization rates while reducing vascular injury. We evaluated angiographic recanalization with TEB alone, intra-arterial delivery of soluble r-tPA alone, or TEB combined with 2 doses of intra-arterial infusion of either the SA-NT or soluble r-tPA. Vascular injury was compared against stent-retriever thrombectomy. Results—: Shear-targeted delivery of r-tPA using the SA-NT resulted in the highest rate of complete recanalization when compared with controls ( P =0.0011). SA-NT (20 mg) had a higher likelihood of obtaining complete recanalization as compared with TEB alone (odds ratio 65.019, 95% confidence interval 1.77, >1000; P =0.0231), intra-arterial r-tPA alone (odds ratio 65.019, 95% confidence interval 1.77, >1000; P =0.0231), or TEB with soluble r-tPA (2 mg; odds ratio 18.78, 95% confidence interval 1.28, 275.05; P =0.0322). Histological analysis showed circumferential loss of endothelium restricted to the area where the TEB was deployed; however, there was significantly less vascular injury using a TEB as compared with stent-retriever procedure (odds ratio 12.97, 95% confidence interval 8.01, 21.02; P <0.0001). Conclusions—: A novel intra-arterial, nanoparticle-based thrombolytic therapy combined with TEB achieves high rates of complete recanalization. Moreover, this approach reduces vascular trauma as compared with stent-retriever thrombectomy. Abstract : Supplemental Digital Content is available in the text.